If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7=(7-x)
We move all terms to the left:
-7-((7-x))=0
We add all the numbers together, and all the variables
-((-1x+7))-7=0
We calculate terms in parentheses: -((-1x+7)), so:We get rid of parentheses
(-1x+7)
We get rid of parentheses
-1x+7
Back to the equation:
-(-1x+7)
1x-7-7=0
We add all the numbers together, and all the variables
x-14=0
We move all terms containing x to the left, all other terms to the right
x=14
| 2(x-8)=-17-2 | | -4–0.2x+11=-0.8x+10X= | | 2(n+5)=-20 | | X+126=168+x+54 | | .5x+.8=1.3 | | -12+4b=2(b-3) | | 2p+13÷5=3 | | -3+6y/2=64 | | 5.3=5.3=5(x-1)+1.4 | | -6(x)=-36 | | (2-2x)+3(x-6)=16-4(6+2x)+x | | -4(-2x-2)+x-2=−49 | | 2p+13÷5=13 | | 15x-14=8x | | q+12=20 | | 14p+5(6.5)=10.25(p+5) | | 10v–6=8= | | 16x-4=4(4x-1) | | -4+-1t+3t^2=0 | | 3(2–x)=5(2x-7)+2 | | 10v–6=8v | | -4+-1t+3t2=0 | | 8v−6v=20 | | 3(x+1)=-2(x-1)/6 | | 3(2x-4)=24x= | | (2x-4)=34 | | 8v6v=20 | | -40+8x=7(7x+6) | | 2|4x-1|=3|4x+2| | | 3x+7=10-22 | | 9a-5a+5=2a-3 | | E^(4x)=26 |